How do you solve #-5( - 3x + 6) + 3= - 117#?

2 Answers
Jan 4, 2018

Answer:

#x# = #-6#

Explanation:

First multiply all the items inside the parentheses by #-5# and then the equation will look like:

#(-5xx-3x+(-5)xx6)+3 = #-117#

or, #15x-30+3# = #-117#

Now, move all numbers to right hand side of the equation, and we get:

#15x# = #-117+30-3#

or, #15x# = #-90#

0r, #x# = #cancel(-90)^6/cancel15^1# = #-6#

Jan 4, 2018

Answer:

#x = -6#

Explanation:

First, use the distributive property:

#-5 ( -3x + 6 ) + 3 = -117#

#-> (-5 * (-3x)) + (-5 * 6) + 3 = -117#

#-> 15x + (-30) + 3 = -117#

Then, combine like terms:

#15x - 30 + 3 = -117#

#-> 15x - 27 = -117#

#-> 15x = -90#

Now, isolate the #x# variable:

#15 x = -90#

#-> x = -90/15#

#-> x = -6#